2010
DOI: 10.4103/0019-5545.64583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration of untreated psychosis on long-term outcome of people hospitalized with first episode schizophrenia

Abstract: Duration of untreated psychosis (DUP) has emerged as a reliable predictor of outcome but continues to remain under scientific scrutiny. The present study examines the effect of differential periods of DUP on long-term outcome of first episode schizophrenia at Mumbai, India. This research was a prospective, 10-year follow-up naturalistic study. Hospitalized patients of first episode schizophrenia were selected and followed up. Results showed that the mean DUP was higher for a group which showed clinical recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Unnatural causes of death accounted for 2 out of 7 deaths, one of which was accidental and other was suicide. A recent study reported the long-term outcome (10 year) of schizophrenia and did not find any relationship between duration of untreated psychosis and good clinical or social outcome (Shrivastava et al 2010). Similar were the observations of Gupta et al (2010).…”
Section: Course and Outcomesupporting
confidence: 61%
See 1 more Smart Citation
“…Unnatural causes of death accounted for 2 out of 7 deaths, one of which was accidental and other was suicide. A recent study reported the long-term outcome (10 year) of schizophrenia and did not find any relationship between duration of untreated psychosis and good clinical or social outcome (Shrivastava et al 2010). Similar were the observations of Gupta et al (2010).…”
Section: Course and Outcomesupporting
confidence: 61%
“…More men were single, and more women were either married or separated. In a 10-year longitudinal follow-up study, Shrivastava et al (2010) showed that compared to non-recovered group, mean duration of untreated psychosis was longer for a group, which showed clinical recovery as assessed on the Clinical Global Impression Scale. A recent study evaluated the predictors of 5-year outcome of patients with schizophrenia and reported that level of insight, number of non-medical explanatory models and individual explanatory models held during the later course of the illness have a significant impact on the outcome (Johnson et al 2012).…”
Section: Course and Outcomementioning
confidence: 99%
“…In particular, a study involving a sample of 58 patients with schizophrenia followed for a mean period of 15 years, demonstrated a reduction in overall functioning and a more severe psychopathology among patients with a DUP of more than 1 year compared to those with a DUP of less than 6 months [16]. On the contrary, several studies present in literature yelded opposite results [15,33-35]. In particular, a study of clinical and psychosocial outcomes in 55 adolescent patients with schizophrenia after a follow-up period of 15 years failed to demonstrate any predictive power of DUP on the different outcome measures considered [33].…”
Section: Discussionmentioning
confidence: 99%
“…An increased number of episodes (or relapses) during the early stages of psychosis is associated with poorer clinical (Birchwood et al, 1998; Emsley et al, 2008) and recovery outcomes (Shrivastava et al, 2010). There is a continued need for early identification and effective treatment options to support those who might be at risk of developing psychosis, as well as those in the early stages of the illness, in order to ensure optimum prognosis (McGlashan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%